Vocal warm-up and breathing training for teachers: randomized clinical trial - Lílian Paternostro de Pina Pereira; Maria Lúcia Vaz Masson; Fernando Martins Carvalho (Universidade de São Paulo, 2015)
OBJECTIVE To compare the effectiveness of two speech therapy interventions, vocal warm-up and breathing training, focusing on teachers' voice quality.METHODS A single-blind, randomized, parallel clinical trial was conducted. The research included 31 20 to 60-year old teachers from a public school in Salvador, BA, Northeasatern Brazil, with minimum workloads of 20 hours a week, who have or have not reported having vocal alterations. The exclusion criteria were the following: being a smoker, excessive alcohol consumption, receiving additional speech therapy assistance while taking part in the study, being affected by upper respiratory tract infections, professional use of the voice in another activity, neurological disorders, and history of cardiopulmonary pathologies. The subjects were distributed through simple randomization in groups vocal warm-up (n = 14) and breathing training (n = 17). The teachers' voice quality was subjectively evaluated through the Voice Handicap Index (Índice de Desvantagem Vocal, in the Brazilian version) and computerized voice analysis (average fundamental frequency, jitter, shimmer, noise, and glottal-to-noise excitation ratio) by speech therapists.RESULTS Before the interventions, the groups were similar regarding sociodemographic characteristics, teaching activities, and vocal quality. The variations before and after the intervention in self-assessment and acoustic voice indicators have not significantly differed between the groups. In the comparison between groups before and after the six-week interventions, significant reductions in the Voice Handicap Index of subjects in both groups were observed, as wells as reduced average fundamental frequencies in the vocal warm-up group and increased shimmer in the breathing training group. Subjects from the vocal warm-up group reported speaking more easily and having their voices more improved in a general way as compared to the breathing training group.CONCLUSIONS Both interventions were similar regarding their effects on the teachers' voice quality. However, each contribution has individually contributed to improve the teachers' voice quality, especially the vocal warm-up.TRIAL RECORD NCT02102399, "Vocal Warm-up and Respiratory Muscle Training in Teachers".